All-Saints Church, Port-of-Spain, Trinidad, B.W.I. - (:unkn) unknown (AnCoG. Agency, 2010)
Image depicts an angular view of the All Saints Church, located in the city of Port of Spain, Trinidad, in the Republic of Trinidad and Tobago.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Anglican church buildings--Trinidad and Tobago; Church buildings--Trinidad and Tobago